Expressão proteica da via PI3K/AKT/mTOR em mastocitomas cutâneos caninos - Ferreira, Marília Gabriele Prado Albuquerque [UNESP] (2014)
The PI3K/AKT/mTOR pathway is related to proliferation, protein synthesis, cell motility and survival. Mutations in this pathway have been associated with the carcinogenic process in diferent tumor types. Currently, specific inhibitors of some proteins such as PI3K, AKT, mTOR, are being tested in order to optimize antitumor therapy in humans and animals. Apart from potential therapeutic targets, increased in immunostaining of some of these proteins have been associated with poorer prognostic in humans tumors. In dogs, mast cell tumor (MCT) is an extremely common skin tumor, which presents a highly variable behavior and unclear etiology. Therefore, the aim of this study was to evaluate the immunostaining of the protein components of PI3K/AKT/mTOR pathway, through the technique of immunohistochemistry, and in a second stage, correlate this results with clinical parameters of patients, with morphological and biological tumor characteristics and the survival time of patients to determine possible prognostic markers for this disease. For this, 46 canine MCTs were used. All tumors were positive in immunohistochemical analysis for the proteins analyzed. Proteins p-AKT Thr 308 and p-S6K1 showed increases in the intensity of immunostaining compared to parameters associated with worse prognosis. These results suggest that the increase in the intensity of immunostaining of p-AKT Thr 308 and p-S6K1 are related to a worse prognosis for dogs affected by cutaneous MCT